Absolute thermometry using hyperpolarized 129Xe free‐induction decay and spin‐echo chemical‐shift imaging in rats. Issue 1 (19th September 2022) - Kern, Agilo L.; Gutberlet, Marcel; Rumpel, Regina; Bruesch, Inga; Hohlfeld, Jens M.; Wacker, Frank; Hensen, Bennet
Abstract : Purpose: To implement and test variants of chemical shift imaging (CSI) acquiring both free induction decays (FIDs) showing all dissolved‐phase compartments and spin echoes for specifically assessing 129 ^129 Xe in lipids in order to perform precise lipid‐dissolved 129 ^129 Xe MR thermometry in a rat model of general hypothermia. Methods: Imaging was performed at 2.89 T. T 2 T_2 of 129 ^129 Xe in lipids was determined in one rat by fitting exponentials to decaying signals of global spin‐echo spectra. Four rats (conventional CSI) and six rats (turbo spectroscopic imaging) were scanned at three time points with core body temperature 37/34/37 ∘ ^° C. Lorentzian functions were fit to spectra from regions of interest to determine the water‐referenced chemical shift of lipid‐dissolved 129 ^129 Xe in the abdomen. Absolute 129 ^129 Xe‐derived temperature was compared to values from a rectal probe. Results: Global T 2 T_2 of 129 ^129 Xe in lipids was determined as 251 . 3 ms ± 81 . 4 ms 251.3 ms± 81.4 ms . Friedman tests showed significant changes of chemical shift with time for both sequence variants and both FID and spin‐echo acquisitions. Mean and SD of 129 ^129 Xe and rectal probe temperature differences were found to be − 0 . 1 5 ∘ C ± 0 . 9 3 ∘ C -0.15^°C± 0.93^°C (FID) and − 0 . 3 8 ∘ C ± 0 . 6 4 ∘ C -0.38^°C± 0.64^°C (spin echo) for conventional CSI as well as 0 . 0 3 ∘ C ± 0 . 7 7 ∘ C 0.03^°C± 0.77^°C (FID) and − 0 . 0 6 ∘ C ± 0 . 7 6 ∘ C -0.06^°C± 0.76^°C (spin echo) for turbo spectroscopic imaging. Conclusion: 129 ^129 Xe MRI using conventional CSI and turbo spectroscopic imaging of lipid‐dissolved 129 ^129 Xe enables precise temperature measurements in the rat's abdomen using both FID and spin‐echo acquisitions with acquisition of spin echoes enabling most precise temperature measurements.